The Effectiveness of G-Sites-Based Learning to Improve Students' Critical Thinking Skills - Akhmad Iswardani; Budi Jatmiko; Eko Hariyono; Habibi; Muhammad Rey Dafa Ahmadi (Journal of Digitalization in Physics Education, 2025)
Objective: This study aims to develop and evaluate the effectiveness of G-Sites-based learning media to improve students' critical thinking skills, particularly in understanding the physics topic of the electrical obstacle series. With the growing need for engaging and flexible digital learning solutions, this research addresses how interactive web-based media can enhance learning outcomes in science education. Method: The research employed a 3D development model consisting of Define, Design, and Develop. Learning needs were identified through student surveys, and the media was designed using G-Sites, which incorporated features such as videos, quizzes, and interactive simulations. The developed media was validated by experts and tested on 59 high school students in a limited classroom trial at SMAN 1 Ngimbang. Data were analyzed quantitatively using validity scores and gain scores from pre-and post-tests. Results: The validation results showed that the learning media was highly valid in terms of design, content, interactivity, and technical aspects, with scores exceeding 90%. Student learning outcomes improved significantly, as shown by increased post-test scores. Feedback indicated that students found the media engaging, accessible, and preferable compared to conventional methods. Novelty: This study introduces the innovative use of Google Sites as a free, accessible, and flexible platform for developing interactive physics learning media. Unlike many commercial platforms, G-Sites allows educators to independently create customized, multimedia-rich content tailored to their students' needs, representing a practical and scalable solution for digital learning in resource-constrained environments.